Republic of Slovenia : Report on the Observance of Standards and Codes-Fiscal Transparency Module. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
This report evaluates the Observance of Standards and Codes on Fiscal Transparency Module for the Republic of Slovenia. Slovenia meets the requirements of the fiscal transparency code in many important respects. The basic legislation and practices are in line with many Organization for Economic Cooperation and Development (OECD) and European Union countries, and there is generally a clear specification of the roles and responsibilities of different institutions. The basic policies for provision of information are consistent with international practices and procedures for budget preparation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet